OPTIMASI TATA KELOLA SEBAGAI UPAYA PENGEMBANGAN OBJEK WISATA MELALUI PENDEKATAN COMMUNITY BASED TOURISM - Muslimah, Wanda; Febiani, Dini; Ulayani, Tina; Mawardi, Faza Pradana; Herwina, Wiwin (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Main issues such as tourism potential, community involvement, and local economic empowerment are crucial in improving the management of tourist attraction development through a Community-Based Tourism (CBT) approach at the Citiis Padakembang Village Tourism Attraction. Thus, this research aims to optimize the governance of the Citiis tourist attraction in Padakembang Village, Tasikmalaya Regency through a Community-Based Tourism (CBT) approach. The method used in this research is qualitative descriptive analysis. Data was collected through group discussion forums, observation, and documentation studies. The research results show that by implementing the CBT approach, the governance of tourist attractions can be significantly improved, resulting in sustainable economic, social, and environmental benefits. Efforts to develop Citiis tourist attractions in Padakembang Village are realized through empowering local communities, active participation in decision-making, as well as responsible maintenance and use of natural resources.